Men's perception of women's dance movements depends on mating context, but not men's sociosexual orientation. (November 2015) - Röder, Susanne; Weege, Bettina; Carbon, Claus-Christian; Shackelford, Todd K.; Fink, Bernhard
Abstract: We investigated the influence of mating context and sociosexual orientation (interest in sex without emotional involvement) on men's perceptions of women's dance movements. One hundred men aged 18 to 33 ( M  = 23.5, SD  = 3.5) years viewed brief videos of five "high attractive" and five "low attractive" female dancers (aged 18 to 22 years; M  = 19.8, SD  = 1.2) from a sample of 84 motion-captured dancers, and judged them on promiscuity and movement harmony. Additionally, half the participants judged the dancers on attractiveness as a long-term mate and the other half on attractiveness as a short-term mate. Men were more attracted to high attractive dancers than to low attractive dancers and judged them higher on attractiveness when choosing as a potential short-term mate. In addition, high attractive dancers were rated higher than low attractive dancers on promiscuity and movement harmony. Specifically, promiscuity judgments predicted men's short-term attractiveness ratings, whereas movement harmony judgments predicted long-term attractiveness ratings. Men's sociosexual orientation did not influence perceptions of female dance movements. Results are discussed with reference to trade-offs in time and energy expenditure on child rearing in men's mate preferences, corroborating the hypothesis that women's body movements inform on these qualities. Highlights: Women's dance movements influence men's attractiveness perceptions. Men's attractiveness perception on women's dance movements depends on mating context. Men's sociosexual orientation does not influence attractiveness ratings of dancers. Perceived promiscuity predicts dancers' attractiveness in short-term mating context. Perceived harmony predicts dancers attractiveness in long-term mating context.